Association between gestational diabetes mellitus and periodontal disease: Systematic review - León-Ríos, X. A. (2022)
Aim: To determine whether there is an association between periodontal disease in pregnant women and the development of gestational diabetes mellitus during their pregnancy. Objetive: To determine if there is an association between periodontal disease in pregnant women and the development of gestational diabetes mellitus during her pregnancy Methods: The present systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA) guidelines. Four electronic data bases were searched: MEDLINE (via PubMed), Cochrane Library, Scopus and Web of Science, through February 2021. Eligible studies were assessed for methodological quality using the Newcastle-Ottawa scale. Results: From 161 studies, 8 were eligible: 3 case-control, 2 cross-sectional and 3 cohort studies. Most of the studies supported an association between periodontitis and GDM. Conclusion: Periodontitis is associated with increased risk for GDM compared to woman without periodontitis. Future robust studies with different designs in distinct populations are needed to enlarge on these findings.